The Correlation between Accounting Systems of Small and Micro Enterprises and Tax Revenue Assessment in Ghana - Nkuah, Joseph Kofi; Frederick, Appiah- Kusi; Asamoah, Kwame (Journal of Education and e-Learning Research, 2015)
The purpose of the study was to find out the correlation between accounting systems of Small and Micro Enterprises and tax revenue assessment. The study was be based on descriptive research survey using questionnaires and interviews as main tools to gather both primary and secondary data to establish the correlation between sound financial record keeping by small /micro and tax revenue assessment. The study showed that most small and micro enterprises have registered with the Registrar General’s Department and that most of them have Tax Identification Numbers (TIN) generated by the Internal Revenue Service. The study further revealed that most small and micro enterprise owners do not have basic knowledge in bookkeeping. From the findings small and micro enterprises spend about half of all cash receipts on cash basis before they are put into bank accounts. Finally, it was established that most of the enterprises cooperate with tax authorities when tax officials come for tax inspection, assessment and collection. It is recommended that, the Internal Revenue Service should ensure effective communication, outreach, monitoring and education of small and micro enterprises on regular basis, to enable the service ensure tax compliance and enhance tax revenue mobilisation from the informal sector in Ghana. Small and micro enterprises should also be encouraged to set up Accounting systems using simple computer software that ensures prompt preparation of financial statements and reporting for tax assessment purposes.